Social Support Systems and Psychosocial Health Conditions: Utilization and Satisfaction among College Students in Chandigarh - Walia, Dinesh Kumar; Kumar, Anuj; Bakshi, Ravleen Kaur; Vashisht, Deepak (Indian Journal of Community Health, 2025)
Background: The COVID-19 lockdown intensified psychosocial challenges for college-going youth due to disrupted routines, social isolation, and financial strains, leading to increased stress and anxiety. Help-seeking difficulties arose from limited access to support services, stigma, and communication or digital barriers. Understanding these difficulties and assessing current readiness levels becomes quintessential to enhance overall resilience and minimize the impact of potential lockdowns in future in this unique demographic. Objectives: To investigate the utilization of social support systems for psychosocial health needs among college-going youth in Chandigarh. To identify barriers to seeking support and gather opinions on improving social support systems in adverse conditions. Methodology: A cross-sectional study was conducted among 265 college going students selected by convenience sampling. Their psychosocial issues, coping mechanisms, help seeking behaviour along with the barriers were investigated through an online survey. Results: There were 149 males and 116 females among 265 participants. A majority of participants i.e. 181 out of 265 (68.3%) affirmed seeking and availing support. The common psychological problems faced by youth during the lockdown included anxiety (62.7%) and nervousness (44.1%). Talking to friends and family (60.1%) and engaging in hobbies (58.5%) were common coping strategies. Help was primarily sought from family (74.5%) and teachers (37.5%). Major barriers for seeking support included fear of reaching out (53.6%) and concerns about mockery (46.8%). For improvement in social support systems, most participants (40.8%) opined in favour of enhanced parental/familial role, and 34.7% suggested developing more support institutions. A substantial proportion (70.9%) felt being unready for future lockdowns, fearing disruptions to their routines and increased isolation. Of the remaining (29.1%) who were ready for another lockdown, 38.9% cited its reason as potential emotional growth, while 36.2% attributed the readiness to learning from previous lockdown. Conclusion: The study shows that a substantial proportion of college youth use social support services, primarily seeking assistance from parents and friends. The main barriers in seeking help were fear and lack of accessibility of support systems. The findings suggest that increasing parental involvement and developing more support systems for college-going youth could significantly improve their social support accessibility and overall psychological well-being.